Sequencing of therapy following first-line afatinib in patients with EGFR mutation-positive non-small cell lung cancer - O'Byrne, Ken (Elsevier, 2019)
Objectives: With the availability of several epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), sequential therapy could potentially render EGFR mutation-positive non-small cell lung cancer a chronic disease in some patients. In this retrospective analysis of EGFR mutation-positive (Del19/L858R) patients receiving first-line afatinib in LUX-Lung 3, 6, and 7, we assessed uptake of, and outcomes following, subsequent therapies including the third-generation EGFR TKI, osimertinib. Methods: Post-progression therapy data were prospectively collected during follow-up. Molecular testing of tumours at progression/discontinuation of afatinib was not mandatory. Duration of subsequent therapies, and survival following osimertinib, were calculated with Kaplan–Meier estimates. Results: Among 553 patients who discontinued first-line afatinib, second-, third- and fourth-line therapy was administered in 394 (71%), 265 (48%), and 156 (28%) patients. The most common post-progression therapy was platinum-based chemotherapy (46%). Thirty-seven patients received subsequent osimertinib, 10 as second-line treatment. Median progression-free survival on afatinib in these 37 patients was 21.9 months. Median duration of osimertinib therapy was 20.2 months; median overall survival was not reached after a median follow-up of 4.7 years. Conclusions: Most patients treated with first-line afatinib received subsequent therapy. Although limited by sample size, enrichment, and a retrospective nature, data from patients who received sequential afatinib and osimertinib are encouraging, warranting further investigation.
Keywords: Afatinib; Non-small cell lung cancer; Osimertinib